BENZOFURAN İÇERİKLİ YENİ KALKON TÜREVLERİNİN SENTEZİ VE BİYOLOJİK ÖZELLİKLERİNİN İNCELENMESİ - AKDOĞAN, ALİ ESAT (Fırat Üniveristesi, 2026)
Bu tez çalışmasında, 4-flor salisil aldehit ve 5-flor salisil aldehit monoklor aseton ile etkileştirilerek asetil benzofuran türevleri (A-B), başlangıç maddeleri olarak sentezlenmiştir. Sentezlenen (A) ve (B) bileşikleri 2,4,5-trimetoksi benzaldehit ve 2-amino benzaldehit ile tepkimeye sokularak claisen-schmidt kondenzasyon reaksiyonu sonucu yeni kalkon türevleri (1-4) sentezlenmiştir. Sentezlenen tüm bileşiklerin karakterizasyonları yapılmıştır. Karakterizasyon teknikleri olarak FT-IR ve 1H-NMR teknikleri kullanılmıştır. Sentezlenen bileşiklerin biyolojik ve dielektrik özellikleri incelenmiştir. Sentezlenen kalkon bileşiklerinin biyolojik özellikleri incelenmiştir. Bu amaç için, antimikrobiyal aktiviteleri incelenmiştir. Antimikrobiyal aktiviteler incelenirken Agar Kuyu Metodu kullanılmıştır. Daha sonra sentezlenen bileşenlerin sitotoksik etkileri incelenmiştir. Bunun için, insan adenokarsinoma (A-549) ve insan kolorektal karsinoma (HCT-116) hücre hatları kullanılmıştır.

In this thesis, acetyl benzofuran derivatives (A-B) were synthesized as starting materials by reacting 4-fluorosalicyl aldehyde and 5-fluorosalicyl aldehyde with monochloroacetone. Synthesized compounds (A) and (B) were reacted with 2,4,5-trimethoxy benzaldehyde and 2-amino benzaldehyde and new chalcone derivatives (1-4) were synthesized as a result of claisen-schmidt condensation reaction. Characterizations of all synthesized compounds were performed. FT-IR and 1H-NMR techniques were used as characterization techniques. Biological and dielectric properties of the synthesized compounds were investigated. Biological properties of synthesized chalcone compounds were investigated. For this purpose, antimicrobial activities were investigated. Agar Well Method was used while investigating antimicrobial activities. Then, cytotoxic effects of synthesized components were investigated. For this, human adenocarcinoma (A-549) and human colorectal carcinoma (HCT-116) cell lines were used.
Synthesis and investigation of biological properties of novel benzofuran-containing chalcone derivatives
Keywords: Kimya